Uncertainties, Limits, and Benefits of Climate Change Mitigation for Soil Moisture Drought in Southwestern North America. Issue 9 (7th September 2021) - Cook, B. I.; Mankin, J. S.; Williams, A. P.; Marvel, K. D.; Smerdon, J. E.; Liu, H.
Abstract: Over the last two decades, southwestern North America (SWNA) has been in the grip of one of the most severe droughts of the last 1, 200 years, with one third to nearly one half of its severity attributable to climate change. We analyze how the risk of extreme soil moisture droughts in SWNA, analogous to the most severe 21‐year (≥ in magnitude to 2000–2020) and single‐year (≥ in magnitude to 2002) events of the last several decades, changes in projections from Phase 6 of the Coupled Model Intercomparison Project. By the end of the 21 st century, SWNA experiences robust ( R ≥ 0.80) soil moisture drying and substantial increases in extreme single‐year drought risk that scale strongly with warming, spanning an 8%–26% probability of occurrence across +2–4 K. Notably, our results show that 21‐year droughts analogous to 2000–2020 are up to 5 times more likely than extreme single‐year droughts under all levels of warming (≈50%). These high levels of 21‐year drought risk are largely invariant across scenarios because of large spring precipitation declines in half the models, shifting SWNA into a drier mean state. Despite projections of this sweeping and ostensibly inevitable increase in 21‐year drought risk, climate mitigation reduces their severity by reducing the magnitude of extreme single‐year droughts during these events. Our results emphasize both the importance of preparing SWNA for imminent increases in persistent drought events and constraining projected precipitation uncertainty to better resolve future long‐term drought risk. Plain Language Summary: Drought is an important natural hazard in southwestern North America, and there is strong evidence that climate change is already increasing the severity of droughts in the region. Using the latest, state‐of‐the‐art climate change projections, we find that warming in the future will increase the risk of both extreme single‐year and 21‐year soil moisture droughts that are similar to major events of the last two decades. Furthermore, we show that while the magnitude of warming has a strong influence on single‐year droughts, even modest warming is likely to lock in an approximately 50% chance of a 21‐year drought similar to 2000–2020 by the end of the 21 st century. The high levels of 21‐year drought risk are driven by large precipitation declines in half the models, which shift the region to a drier mean state under even the lowest warming scenario. Despite the apparent insensitivity of 21‐year drought risk to mitigation measures, our results still demonstrate the value of climate change mitigation for reducing future drought severity and single‐year extreme drought risk in the region. Our study also highlights the importance of precipitation responses in the models as major uncertainties that must be resolved to increase our confidence in these projections. Key Points: Models project higher risk of soil moisture droughts like the recent event in southwestern North America by 2100 Climate mitigation minimally reduces 21‐year drought risk because half the ensemble projects large precipitation declines in all scenarios Mitigation reduces the magnitude of extreme single‐year droughts, even during longer events, making high‐risk droughts less severe